Effects of differential nitrogen application on wheat grain proteome. (November 2021) - Liu, Peixun; Ma, Xiaofei; Wan, Hongshen; Zheng, Jianmin; Luo, Jiangtao; Hu, Yuanbin; Pu, Zongjun
Abstract: Wheat, an important human energy source, is critical for global food security. Grain hardness is a major determinant of wheat quality. Although the genetic bases of wheat grain hardness have been investigated, the mechanisms underlying the effects of nitrogen on wheat quality remain largely unknown. In the same wheat cultivar, grain hardness and protein content decreased in plants treated with low nitrogen as compared to those treated with high nitrogen, while starch content increased. High-throughput tandem mass tags (TMT) quantitative proteomics identified 6061 effective proteins in cultivar Shumai 969; 88 of these proteins were differentially expressed in the low-nitrogen plants as compared to the high-nitrogen plants (31 upregulated and 57 downregulated). Several storage proteins, including α-gliadins, γ-gliadins, ω-gliadins, high molecular weight glutenin subunits, and three globulin proteins, were downregulated in the low-nitrogen plants as compared to the high-nitrogen plants. The differentially expressed proteins associated with the 10 significantly enriched Gene Ontology terms and the 5 significantly enriched biochemical metabolic pathways might play a role in the determination of wheat grain hardness. This study provides a baseline for the effects of nitrogen application on wheat grain quality and identifies candidate genes for the targeted breeding of superior wheat varieties with specific end-use properties. Graphical abstract: Image 1 Highlights: TMT provided high-throughput, high-resolution protein quantification. Wheat grain hardness and protein content decreased after low-N treatment. Storage proteins and some globulins responded mainly to nitrogen fertilizer. DEPs provided candidate genes for genetic improvement of wheat grain quality.